Nonlinear dynamics of femtosecond laser interaction with the central nervous system in zebrafish - Jun, Soyeon; Jun, Soyeon; Herbst, Andreas; Herbst, Andreas; Scheffter, Kilian; John, Nora; Kolb, Julia; Wehner, Daniel; Fattahi, Hanieh (Communications Physics, 2024)
Understanding the photodamage mechanism underlying the highly nonlinear dynamic of femtosecond laser pulses at the second transparent window of tissue is crucial for label-free microscopy. Here, we report the identification of two cavitation regimes from 1030 nm pulses when interacting with the central nervous system in zebrafish. We show that at low repetition rates, the damage is confined due to plasma-based ablation and sudden local temperature rise. At high repetition rates, the damage becomes collateral due to plasma-mediated photochemistry. Furthermore, we investigate the role of fluorescence labels with linear and nonlinear absorption pathways in optical breakdown. To verify our findings, we examined cell death and cellular responses to tissue damage, including the recruitment of fibroblasts and immune cells after irradiation. These findings contribute to advancing the emerging nonlinear optical microscopy techniques and provide a strategy for inducing precise, and localized injuries using near-infrared femtosecond laser pulses.
CRIS-Team Scopus Importer:2024-05-31